PENGARUH PEMBERDAYAAN, KARAKTERISTIK PEKERJAAN DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN DENGAN MEDIASI KOMITMEN ORGANISASIONAL (STUDI PADA LPK KABUPATEN BATANG) - Muh. Mizan Sya’roni, 124202.0091 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to analyze the Influence of empowerment, job characteristics, and motivation on employee job satisfaction with the mediation of organizational commitment study on LPK, Batang. This research is expected to produce a useful analysis to provide empirical information about the influence of personality, empowerment, organizational citizenship behavior on employee performance with moderated social capital that can be considered to improve human resources. To examine the relationship between variables, the researchers used a technique Census, data analysis using SPSS 20.00. Data were collected by using kuesinoer given to respondents study population 110 employees and entirely used as samples, while the samples were processed 110 respondents. Tests on research conducted by the test instrument validity (factor analysis) and coefficient alpha reliability test while statistical testing tool used is multiple regression analysis, t-test, R2.The results showed that the variables tested Overall, namely empowerment, job characteristics, motivation, organizational commitment and job satisfaction expressed both by respondenyaitu LPK employees throughout Batang district. Disampingitu, empowerment, motivation and organizational commitment expressed by the respondents could have an impact in improving job satisfaction, whereas job characteristics had no significant effect. The increase of the variable empowerment, motivation and organizational commitment has a positive contribution to the increase in employee satisfaction.Of mediation known test of organizational commitment as a mediating variable is less effective indirect effect between empowerment and motivation on employee job satisfaction. Empowerment and motivation on employee job satisfaction. Empowerment and motivation more effectively direct effect on job satisfaction. While the job characteristics do not affect the organizational commitment not mediate the effect of empowerment on job satisfaction and motivation.Â Keywords: Empowerment, Job Characteristics, Motivation, and JobSatisfaction,